2022
DOI: 10.1029/2022je007268
|View full text |Cite
|
Sign up to set email alerts
|

Life Underground: Investigating Microbial Communities and Their Biomarkers in Mars‐Analog Lava Tubes at Craters of the Moon National Monument and Preserve

Abstract: Although robotic missions to Mars have focused on surface measurements, astrobiologists are beginning to shift their attention underground. The surface of Mars is extremely challenging for life or its traces: it is seared by ultraviolet radiation and cosmic rays and subject to widely fluctuating surface temperatures (Pavlov et al., 2012).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 126 publications
0
1
0
Order By: Relevance
“…Nitrosococcales lineage wb1‐P19 (OTU 4), seen in over half of GA samples, was initially characterized as a possible chemolithotroph (Holmes et al., 2001) and has been since been described by others as having N cycling roles (Martin‐Pozas et al., 2022). wb1‐P19 has been identified in diverse cave types, including Weebubbie Cave in Australia (Holmes et al., 2001), a hypogene SAS cave in Italy (Jurado et al., 2020), and even volcanic caves (Weng et al., 2022). Top BLAST matches to the representative sequence of OTU 4 include several cave‐related sequences such as moonmilk from a limestone cave, cave biofilms, and microbial mats from lava tubes (accession numbers LT798869.1, HE602908.1, LR130706.1, OK182161.1, and KC331752.1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrosococcales lineage wb1‐P19 (OTU 4), seen in over half of GA samples, was initially characterized as a possible chemolithotroph (Holmes et al., 2001) and has been since been described by others as having N cycling roles (Martin‐Pozas et al., 2022). wb1‐P19 has been identified in diverse cave types, including Weebubbie Cave in Australia (Holmes et al., 2001), a hypogene SAS cave in Italy (Jurado et al., 2020), and even volcanic caves (Weng et al., 2022). Top BLAST matches to the representative sequence of OTU 4 include several cave‐related sequences such as moonmilk from a limestone cave, cave biofilms, and microbial mats from lava tubes (accession numbers LT798869.1, HE602908.1, LR130706.1, OK182161.1, and KC331752.1).…”
Section: Discussionmentioning
confidence: 99%
“…LGA19_14BB Cave in Australia (Holmes et al, 2001), a hypogene SAS cave in Italy (Jurado et al, 2020), and even volcanic caves (Weng et al, 2022).…”
Section: Mineral-associated Microbial Communitiesmentioning
confidence: 99%
“…Nitrosococcales lineage wb1-P19 (OTU 4), seen in over half of GA samples, was initially characterized as a possible chemolithotroph (Holmes, 2001) and has been since been described by others as having N cycling roles (Martin-Pozas et al, 2022). wb1-P19 has been identified in diverse cave types, including Weebubbie Cave in Australia (Holmes et al, 2001), a hypogene SAS cave in Italy (Jurado et al, 2020), and even volcanic caves (Weng et al, 2022). Top BLAST matches to the representative sequence of OTU 4 include several cave related sequences such as moonmilk from a limestone cave, cave biofilms, and microbial mats from lava tubes (accession numbers LT798869.1, HE602908.1, LR130706.1, OK182161.1, and KC331752.1).…”
Section: Mineral-associated Microbial Communitiesmentioning
confidence: 99%
“…Riquelme et al [19] recovered representatives of Euzebyales from colored microbial mats found in volcanic caves in the Azores, Hawai'i, and New Mexico, and stated that the different clades obtained suggested a significant diversity within the sequences found. Other papers reported Euzebya sequences from caves in different geographical regions [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] (Table 1).…”
Section: Metagenomic Detection Of Euzebya In the Environment: Cavesmentioning
confidence: 99%
“…The advent of molecular tools, particularly next-generation sequencing (NGS), has dramatically changed the knowledge of the diversity of microbial life on Earth. In recent decades, many studies on different terrestrial environments, including caves [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], have described the diversity and abundance of Euzebyales/Euzebyaceae/Euzebya; however, as far as we know, no Euzebya isolates have been obtained from terrestrial niches. This prompted us to review the habitats where Euzebya sequences were found and their ecological requirements in order to understand the failures in the adoption of isolation protocols that led to the lack of terrestrial isolates.…”
Section: Introductionmentioning
confidence: 99%